(untitled) (Research, Society and Development, 2020)
This study aims to analyze the perceptions of students of technical education integrated about the existing relationships between emotions and assessment of learning at school. The methodology used is characterized as qualitative with a phenomenological approach. Through a semi-structured questionnaire applied to 174 students from the Instituto Federal Farroupilha, we seek to understand how these relations are shown in the referred context. In the data analysis, carried out under the bias of Discursive Textual Analysis (DTA), we observed that proof is the most used assessment tool in the context, although it is not the only and coexist with a variety of forms of assessment. As for emotions in the evaluation process, negative ones predominate, such as anxiety and fear, associated with physiological reactions such as difficulty in concentration, headache, and memory lapses. However, positive emotions were also pointed out, such as joy and pleasure, associated with different assessment instruments than tests and exams, especially those that are more practical and flexible, such as research or debates.